Synthesis, biological evaluation and molecular docking studies of chromone hydrazone derivatives as α-glucosidase inhibitors. Issue 13 (1st July 2017) - Wang, Guangcheng; Chen, Ming; Wang, Jing; Peng, Yaping; Li, Luyao; Xie, ZhenZhen; Deng, Bing; Chen, Shan; Li, Wenbiao
Graphical abstract: Highlights: Synthesis of a novel series of chromone hydrazone derivatives. Compounds were evaluated in vitro α -glucosidase inhibitory activity. Compound4d was found to be the most active compound. Molecular docking study showed the good interaction of compounds with α -glucosidase. Abstract: A series of chromone hydrazone derivatives4a –4p have been synthesized, characterized by 1 H NMR and 13 C NMR and evaluated for their in vitro α -glucosidase inhibitory activity. Out of these tested compounds, six (4a, 4b, 4d, 4j, 4o and4p ) displayed potent α -glucosidase inhibitory activity with IC50 values in the range of 20.1 ± 0.19 μM to 45.7 ± 0.23 μM, as compared to the standard drug acarbose (IC50 = 817.38 ± 6.27 μM). Among this series, compound4d (IC50 = 20.1 ± 0.19 μM) with 4-sulfonamide substitution at phenyl part of hydrazide was found to be the most active compound. Lineweaver-Burk plot analysis indicated that compound4d is a non-competitive inhibitor of α -glucosidase. The binding interactions of the most active analogs were confirmed through molecular docking studies. Docking studies showed4d are interacting with the residues Glu-276, Asp-214, Asp-349 and Arg-439 through hydrogen bonds, arene-anion and arene-cation interactions. In summary, our studies shown that these chromone hydrazone derivatives are a new class of α -glucosidase inhibitors.